Evaluation and Comparision of Total Phenolics, Total Flavonoids and Antioxidant Activity of A. Mexicana Aerial Parts in Different Solvents - Sachin Kumari (Journal of Antioxidant Activity, 2023)
The study's goal was to determine the total phenolics, total flavonoids, and antioxidant activity of A. mexicana aerial parts. Extracts were prepared using different solvents namely n-hexane, ethyl acetate, acetone, methanol, and water on basis of increasing polarity using soxhlet appratus. Aqueous extract from the flower contained the highest level of total phenolics, followed by that of the stem and leaves. The flower methanol extract was found to contain the most total flavonoids. With IC50 values of 24.98 g/ml in acetone extract, the stem component demonstrated the most DPPH (1,1-diphenyl-2-picrylhydrazyl) free radical scavenging activity, followed by leaves with IC50 values of 36.29 g/ml in hexane extract and flowers with IC50 values of 38.33 g/ml in acetone extract. FTIR analysis showed that the presence of phenols and flavanoids. In different solvents, the DPPH free radical scavenging activity of aerial portions of A. mexicana varied greatly, and it increased with increasing concentration levels. In terms of antioxidant potency, higher amounts of total phenolics in aqueous extract, total flavonoids in methanol extract, and acetone extract were shown to be the most potent antioxidant. The aerial parts of A. mexicana have a considerable amount of flavanoids, phenolics, and antioxidant activity.
Keywords: Extract